Rare Case of Bilateral Elbow Dislocation with Radial Head Fractures in a 33 Year Male - A. Raviraj; Vidyasagar Maalepati; K. Abhishek Sugumar; Vivek Kumar N. Savsani; Viresh B. Murgodi; F. N. P. Bianca E. Bullie; Ashish Anand (Perspective of Recent Advances in Medical Research Vol. 9, 2023)
A 33-year-old man presented with a rare case of bilateral elbow dislocation with associated radial head fractures. Following road traffic accident patient presented to the emergency room, the elbow dislocations were treated there, the left radial head fracture was treated conservatively for four weeks in an above elbow slab, and the right radial head and neck fracture was treated surgically with Herbert screw fixation for the radial head fracture and buttress plating for the radial neck fracture. At the six-month checkup, the patient reported no pain and great range of motion in both flexion and extension, with pronation and supination of the elbows reaching 50o and 40o for the right elbow and 60o and 45o for the left, respectively.